(untitled) (International Journal of Graphic Design, 2026)
This study explores the visual articulation of Malay cultural identity in children’s educational media through digital-based picture storybooks. Although visual storytelling has great potential as a medium for cultural literacy, the transmission of traditional values into child-friendly aesthetics often faces challenges between cultural authenticity and visual simplification. Using a qualitative approach with a formal design framework, this study applies Charles Sanders Peirce’s semiotic analysis and visual communication principles to dissect elements of composition, typography, visual hierarchy, and color psychology in storybooks for children aged 5–9 years. Data were collected through a triangulation methodology involving comparative visual analysis, audience studies of children, and expert judgment validation. The analysis results indicate that the transformation of Malay identity—such as the bamboo shoot motif and traditional color palette—can be effectively integrated without losing its philosophical meaning through the application of simple geometric shapes (child-friendly shapes). Furthermore, empirical validation confirms that a coherent visual storytelling structure significantly improves children’s cognitive retention and emotional attachment to local cultural values. This research contributes to the methodology of visual communication design, particularly in formulating standard guidelines for creating measurable cultural literacy media for the younger generation.